Brand Image Mediates Product Quality and Electronic Word of Mouth Towards Purchase Decision - I Wayan Awi Marwida; Putu Yudy Wijaya; Widani Sugianingrat Ida Ayu Putu (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The purpose of this research was to identify and analyze the role of Brand Image in mediating Product Quality and Electronic Word of Mouth on Purchase Decisions at Taman Prakerti Bhuana consumers. The research population is consumers of Taman Prakerti Bhuana whose number is unknown. The sampling technique used was purposive sampling with 102 respondents. The research instruments used were questionnaires, observation, interviews and literature and analysis methods used were descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square (SEM-PLS) analysis. The results of the research show that product quality, eWOM and brand image have a positive and significant effect on purchase decision, product quality and eWOM have a positive and significant effect on brand image, brand image can positively and significantly mediate the effect of product quality and eWOM on purchase decision. The implication of the research is for Prakerti Bhuana Park to provide the best service as much as possible so that product quality and eWOM are still perceived very well by consumers so that it will have implications for increasing purchase decisions at Prakerti Bhuana Park. Researchers suggest to Prakerti Bhuana Park to be able to evaluate and innovate in efforts to increase product quality and eWOM so that it has implications for increasing consumer purchase decisions.